Juridic Review Concerning Supervision of Financial Services Authorities in Insurance Companies Based on Law Number 40 of 2014 Concerning Insurance - Sufmi Dasco Ahmad (Enrichment : Journal of Management, 2022)
The development of the insurance business in Indonesia is growing rapidly along with the increasing number of people who want to transfer the risks they will face to the insurance company. Risk in insurance is the uncertainty of the occurrence of an event that can cause economic losses. There are many changes in the Insurance Law, one of which is about regulation and supervision. The regulation and supervision in the old law was carried out by the Ministry of Finance, while the new law was supervised by the OJK. The Financial Services Authority carries out supervision so that non-bank financial service institutions fulfill their promises to customers. In order to achieve this goal, a supervisory system is needed that can provide an early indication of the potential failure of non-bank financial services institutions. The method used in this research is descriptive analytical with a normative juridical approach. Data collection techniques through literature review are complemented by field studies to obtain primary data to support secondary data. Data analysis was carried out qualitatively. The results of the study state that the Financial Services Authority can take necessary actions including appointing a statutory manager, the appointment is made if the management of the insurance company is considered detrimental to consumers so that management is needed that can represent the interests of OJK and consumers. One of the tasks of the statutory manager is to save the wealth of the insurance company. Supervision is carried out periodically and/or at any time. The scope of OJK supervision is all aspects of the insurance business operator or certain aspects of the insurance business activity. As for some suggestions that the author would like to convey is that OJK is expected to conduct socialization to the public in general and insurance companies in particular. It is intended that the public and insurance companies understand the functions and duties of statutory managers. Weak supervision in the insurance sector caused by a lack of supervisory staff at the OJK institution, so that OJK often misses the point in conducting supervision. So that the OJK does not fall short in supervising, the OJK should improve its performance by adding more supervisors for the insurance industry. This is intended so that no insurance company commits fraud that results in harming the community.